Developing Metrics for Assessing Engineering Instruction: What Gets Measured is What Gets Improved - King, Judson C.; Ambrose, Susan A.; Arreola, Raoul A.; Watson, Karan (The National Academies Press, 2009)
Faculty in all disciplines must continually prioritize their time to reflect the many demands of their faculty obligations, but they must also prioritize their efforts in ways that will improve the prospects of career advancement. The current perception is that research contributions are the most important measure with respect to faculty promotion and tenure decisions, and that teaching effectiveness is less valued–regardless of the stated weighting of research, teaching and service. In addition, methods for assessing research accomplishments are well established, even though imperfect, whereas metrics for assessing teaching, learning, and instructional effectiveness are not as well defined or well ...